2006
DOI: 10.1021/jf061342c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Odor-Active Compounds in Unhopped Beer and Beers Hopped with Different Hop Varieties

Abstract: Odorants comprising the hop aromas of beers were examined. Strongly hopped beers with Saazer, Hersbrucker, and Cascade hops were compared with unhopped beer by gas chromatography-olfactometry (CharmAnalysis) and sensory evaluation. Twenty-seven odorants were revealed as hop-derived, which derived either directly from hops or via metabolization, and 19 components were identified. Of the components, linalool, geraniol, ethyl 2-methylbutanoate, ethyl 3-methylbutanoate, and ethyl 2-methylpropanoate were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
160
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(178 citation statements)
references
References 17 publications
9
160
2
6
Order By: Relevance
“…Linalool is one of the key odourants that impart a fl oral, fruity and citrus note to the Cascade and Perle hops (33,34) used in this study. More importantly, linalool is also one of the hop-derived odourants in hopped beer, indicating that the presence of this terpenoid in beer comes at least partly from wort (35,36). However, the concentration of linalool found in the beer can be aff ected by yeast metabolism (37).…”
Section: Changes In Volatile Compositionmentioning
confidence: 99%
“…Linalool is one of the key odourants that impart a fl oral, fruity and citrus note to the Cascade and Perle hops (33,34) used in this study. More importantly, linalool is also one of the hop-derived odourants in hopped beer, indicating that the presence of this terpenoid in beer comes at least partly from wort (35,36). However, the concentration of linalool found in the beer can be aff ected by yeast metabolism (37).…”
Section: Changes In Volatile Compositionmentioning
confidence: 99%
“…The volatile compounds found in hops are transferred to beer, and these derived-volatile components have an influence on the aroma of beer (Sandra et al, 1975;Tressl, Friese, Fendesack, & Köppler, 1978c;Kishimoto, Wanikawa, Kono, & Shibata, 2006;Takoi et al, 2009). Sandra et al (1975) have stressed the contribution of 3-methylbutanoic acid, 2-methylbutanoic acid, and 4-methyl-3-pentenoic acid to the flavor of beer because these compounds in hop-containing beer are present in higher concentration than those in hop-free beer.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report showed that the oxygenated sesquiterpenoid fraction from hops contributed to its spicy character (15), but mechanisms underlying this have not been well studied. Previous reports have implied that characteristic ingredients of HHE essential oil can modulate sensory receptors such as TRP channels (14,15).…”
Section: The Transient Receptor Potential (Trp)mentioning
confidence: 99%
“…A particular hop cultivar, Hallertau Hersbrucker (HHE), is described as adding a "spicy" character to beer (14). A previous report showed that the oxygenated sesquiterpenoid fraction from hops contributed to its spicy character (15), but mechanisms underlying this have not been well studied.…”
Section: The Transient Receptor Potential (Trp)mentioning
confidence: 99%